Wetting geometry and deposition patterns manipulation with bi-dispersed particle-laden droplets - Lim, Si Xian (2024)
Polygonal deposition through evaporation of the suspension droplets holds promise for printing applications. The distinctive edges present in polygonal droplets offer the potential to enhance printing resolution and enable the fabrication of diverse thin depositions. Prior investigations revolve one dimensional control with the types of wetting geometries and deposition patterns initiate from different driving factors. The current study delves into the synergistic interplay between a bi-dispersed suspension mixing ratio and particle concentration, as they collectively influence the deposition pattern of octagonal droplets formed using a micropyramid cavity patterned substrate. The investigation culminates in the development of a comprehensive phase diagram categorizing four distinct types of deposition: octagonal outer-ring deposition, octagonal ring with irregular features, octagonal uniform deposition, and central deposition. Specifically, octagonal outer-ring deposition is observed when droplets consist predominantly of 3μm particles at lower concentrations. In cases where a suspension contains 10μm particles, an intermediate concentration exceeding 50% gives a rise to the octagonal outer-ring deposition intermingled with irregular features. The octagonal uniform deposition emerges when 3μm particles, co-aggregated with 10μm particles, are compelled to settle at the deposition center within the mixture at the 3:1 ratio at 1.0 wt% and 2.6 wt%. Notably, the “curvature effect”, exhibited by the aggregates adhering to the liquid–air interface, counter-intuitively suppresses octagonal deposition despite the presence of octagonal wetting geometry and forms the central deposition. In summary, the study introduces a robust method to achieve the uniform deposition and proposes a scalable and flexible strategy for generating diverse deposition types through the judicious mixing of two suspension solutions at distinct weight ratios.